2015
DOI: 10.1155/2015/321602
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-Based Immunosuppression as GvHD Prophylaxis after Bone Marrow Transplantation for Severe Aplastic Anaemia: A Case Report and Review of the Literature

Abstract: Congenital or acquired severe aplastic anaemia (SAA) is cured by bone marrow transplantation (BMT) from a histocompatible leukocyte antigen- (HLA-) identical sibling. The best conditioning regimen is cyclophosphamide (CTX) with or without antithymocyte globulin (ATG), followed by short-term methotrexate (MTX) and cyclosporine A (CsA) to prevent graft-versus-host disease (GvHD). In our pediatric oncology-hematology unit, a 5-year-old girl with SAA was treated with two BMT from the same HLA-identical sibling don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Suppression immunotherapy focuses on dampening an abnormal immune response as is the case for autoimmune diseases or allogeneic organ of cell transplantation. Currently, the use of immunosupressive drugs such as glucocorticoids which inhibit cell-mediated immunity (Varga et al, 2014), cytostatics (i.e., methotrexate; Pulsipher et al, 2014) and newer drugs acting on immunophilins such as sirolimus (Perruccio et al, 2015) have had tremendous impact on improving organ-graft survival rates (Murray et al, 1963;Hariharan et al, 2000) and amelioration of autoimmune diseases (Brugos et al, 2014;Hou et al, 2014). However, these agents are associated with adverse off target effects, which can result in substantial accumulated morbidity over their required life-long use, including an alarming increase in cancer rates.…”
mentioning
confidence: 99%
“…Suppression immunotherapy focuses on dampening an abnormal immune response as is the case for autoimmune diseases or allogeneic organ of cell transplantation. Currently, the use of immunosupressive drugs such as glucocorticoids which inhibit cell-mediated immunity (Varga et al, 2014), cytostatics (i.e., methotrexate; Pulsipher et al, 2014) and newer drugs acting on immunophilins such as sirolimus (Perruccio et al, 2015) have had tremendous impact on improving organ-graft survival rates (Murray et al, 1963;Hariharan et al, 2000) and amelioration of autoimmune diseases (Brugos et al, 2014;Hou et al, 2014). However, these agents are associated with adverse off target effects, which can result in substantial accumulated morbidity over their required life-long use, including an alarming increase in cancer rates.…”
mentioning
confidence: 99%
“…In another study, it was found that sirolimus induces adipogenic differentiation, and this was associated with hyperlipidemia, which is a side effect of sirolimus (16). There are also studies showing the use of sirolimus to prevent GVHD after allogenic stem cell transplants (20,21). Several randomized studies with kidney transplantation have shown that the immunosuppressive regimen established with the addition of sirolimus is associated with allograft survival and long-term renal function after transplantation (21).…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies showing the use of sirolimus to prevent GVHD after allogenic stem cell transplants (20,21). Several randomized studies with kidney transplantation have shown that the immunosuppressive regimen established with the addition of sirolimus is associated with allograft survival and long-term renal function after transplantation (21). In these studies, the relationship between BMSCs and sirolimus with each other has not been investigated, and this there is a knowledge gap in the literature, regarding co-effect of immunosuppressive drugs and MSCs on MSCs.…”
Section: Discussionmentioning
confidence: 99%